LABOR’S SKILL DEVELOPMENT STRATEGY FOR SMALL BUSINESS (SMEs) IN CHIANG RAI PROVINCE TO SUPPORT ECONOMIC DEVELOPMENT IN THE MEKONG SUB-REGION - Khamdee, Wisit; Boonnun, Vikrom; Promjaisa, Nawin; Muangkasem , Benjamat (Academic Journal Phranakhon Rajabhat University, 2024)
This article aims to: 1) propose strategies for labor skill development for small-sized enterprises (SMEs) in Chiang Rai province by conducting focus group discussions with stakeholders at the policy level regarding labor skill development in the province, and 2) draft a strategy for labor skill development by analyzing the current situation of the labor force in the province (SWOT Analysis), analyzing the current strategic position of the labor force situation in the province (TOWS Matrix Analysis), and drafting a strategy for labor skill development for SMEs in the province to contribute to the economic development in Mekong Sub-region countries. The findings have led to the following strategic issues: 1) enhancing the development of personnel capabilities to meet international standards, 2) developing a standard work system that supports international trade, 3) upgrading the information technology system to support production and investment trade, 4) improving the human resources development curriculum for production and service, and 5) integrating collaboration between government and private sectors in border areas.